First-Trimester Sequential Screening for Preeclampsia Using Angiogenic Factors: Study Protocol for a Prospective, Multicenter, Real Clinical Setting Study - Trilla, Cristina; Luna, Cristina; De León Socorro, Silvia; Rodriguez, Leire; Ruiz-Romero, Aina; Mora Brugués, Josefina; Benítez Delgado, Taysa; Fabre, Marta; Martin Martínez, Alicia; Ruiz-Martinez, Sara; Llurba, Elisa; Oros, Daniel (Frontiers in Cardiovascular Medicine, 2022)
Introduction: The incidence of preeclampsia is about 2-8%, being one of the leading causes of perinatal morbidity and maternal mortality in the world. Early prophylactic low dose administration (150 mg) of acetyl salicylic acid, is associated with a significant reduction in the incidence of early-onset preeclampsia, intrauterine growth restriction and neonatal mean stay in Intensive Care Unit. Universal implementation of first-trimester screening system including angiogenic and antiangiogenic markers (PlGF and/or sFlt-1) has shown a prediction rate of 90% for early-onset preeclampsia, but entails a high financial cost. The aim of this study is to prospectively determine, in a real clinical setting, the predictive and preventive capacity of a universal preeclampsia first trimester two-step sequential screening model, determining Placental Growth Factor (PlGF) only in those patients previously classified as intermediate risk by means of a multivariant model based on resources already used in the standard pregnancy control. We hypothesize that this screening model will achieve similar diagnostic performance as the universal determination of PlGF, but at a lower economic cost. Methods and Analysis: This is a prospective, multicentric, cohort study in a real-world clinical setting. Every singleton pregnancy will be recruited at the routine first pregnancy visit. In a first step, first-trimester risk of preeclampsia will be calculated using a multivariate Gaussian distribution model, based on based on medical history, mean blood Pressure, Pregnancy-Associated Plasma Protein A (PAPP-A) and Uterine Artery Doppler Pulsatility Index (UTPI). Patients will be classified into three risk groups for preeclampsia: 1) risk ≥ 1/50, high-risk with no further testing (blinded PlGF), 2) risk between 1/51 and 1/500, medium-risk requiring further testing and, (3) risk ≤ 1/501, low-risk with no further testing. In a second step, Placental Growth Factor (PlGF) will only be determined in those patients classified as intermediate risk after this first step, and then reclassified in high or low-risk groups. Prophylactic administration of aspirin (150 mg per day) will be prescribed only in high risk patients. As a secondary objective, soluble fms-like Tyrosine Kinase-1 (sFTL) values will be blinded determine in patients with high and intermediate risk, to assess its potential screening performance.